Power limits with adjustable 10G receiver parameters for A-RoF transmission - Kurbatska, Inna; Ostrovskis, Armands; Skladova, Laura; Rubuls, Kristaps; Spolitis, Sandis; Bobrovs, Vjaceslavs (Elektronika ir Elektrotechnika, 2023)
Current paper characterizes the performance of the three-radio-frequency-channels, orthogonal-frequency-division-multiplexed (OFDM) radio-over-fiber (RoF) transmission system in terms of error-vector-magnitude and received optical signal power for a typical 10 GHz receiver obtained by the comprehensive simulations. The impact of the transmitted OFDM channels' signal-to-noise ratio (SNR) is also considered. We demonstrate that the SNR decrease from 40 dB to 25 dB results in an error vector magnitude (EVM) increase of up to 4 %. Furthermore, we propose the approach for allowing adjusting these results to other receiver sensitivity and responsivity values by introducing a delta in received optical signal power eliminating additional simulation or complicated calculations. The feasibility of the adjustments with a precision of up to 0.001% of the EVM is proved.